Sarah Kirsch, auteur d’ouvrages pour enfants - Céline Weck (Recherches Germaniques)
Sarah Kirschs Activities as an Author of Children’s LiteratureThis contribution will highlight three works of children’s literature written by Sarah Kirsch (1935-2013) at the beginning of her poetic career. On the one hand, the aim is to point out these productions, which are often considered to be of secondary importance, and on the other hand to reveal the specific literary techniques of Sarah Kirsch, which are already at work in these early pieces. First, an example of children’s literature commissioned by the GDR literary authorities (Zwischen Herbst und Winter) and strongly influenced by the guidelines of socialist realism will be examined, followed by a scientifically resonant rewriting of Carroll’s Alice’s Adventures in Wonderland (Caroline im Wassertropfen). The final part of this contribution will identify the techniques of simplification and trivialisation of popular literary material that Sarah Kirsch makes extensive use of, both in her productions for children and in her poetic work.